Peran Konsep Diri, Minat dan Kebiasaan Belajar Peserta Didik terhadap Prestasi Belajar Fisika - Purni Munah Hartuti (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2015)
The objective of this reseacrh is to analyze the effect of self-concept, interest and habbits of student study on the learning achievement of physics. The methode of this research is using survey with correlation and multiple regression used SPSS version 17.0. The finding of this reseacrh are self concept , interest and habbits of student study influenced together on the learning achievement of physics for 89,8 %. It means 89,8 % the learning achievement of physics described by Self concept student, Interest of student study and habbits of student study influenced together. Teachers in education field should be able to improve self concept to their students and improve the way how to teach in good way to get the learning interest of their student. Also they can give support to their students to do good learning habit.